Literature from a computer: When there are "authors" without poetical consciousness writing - Franta, Tomáš (Bohemica Olomucensia, 2017)
This study focuses on the phenomenon of generative literature. It gives a condensed chronological overview of generetive literature in Czechia, Slovakia and worldwide from 1950s till the present time. Focusing on most significant pieces of generative literature it shows evolutionary tendencies within this field and gives a brief reflection about autorship, originality and future of generative literature.
Keywords: generative literature; electronic literature; artificial intelligence; artificial neural network; interactive fiction; interactive drama; chatbot